Clonal relationship among invasive and non-invasive strains of enteroinvasive Escherichia coli serogroups - Martinez, Marina B.; Whittan, Thomas S.; McGraw, Elizabeth A.; Rodrigues, Josias [UNESP]; Trabulsi, Luiz R. (My University, 1999)
The genetic relatedness among 96 invasive Escherichia coli belonging to several serogroups and 13 non-invasive of several serotypes that share the same O antigen was investigated by multilocus enzyme electrophoresis analysis. The invasive strains were isolated in different parts of the world and most of them recovered from dysentery. Twenty-nine electrophoretic types were distinguished and the most invasive strains were found to belong to two major lineages. These results suggested that the invasive ability in these strains has evolved in divergent chromosomal backgrounds, presumably through the horizontal spread of plasmid-borne invasion genes. The maintenance of invasive phenotypes in separate lineages suggests that this ability confers a selective advantage to invasive strains. Copyright (C) 1999 Federation of European Microbiological Societies.
Keywords: Clonal relationship; Enteroinvasive Escherichia coli; Genetic polymorphism; Multilocus enzyme electrophoresis; o antigen; cell invasion; diarrhea; electrophoresis; escherichia coli; genetic analysis; genetic distance; genetic polymorphism; human; nonhuman; phylogeny; priority journal; serotype; Dysentery; Electrophoresis, Starch Gel; Escherichia coli; Humans; Phenotype; Polymorphism, Genetic; Sequence Analysis, DNA; Serotyping